2011
DOI: 10.1177/0164027511411928
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Social Relationships and Emotional Well-Being in Middle-Aged and Older African Americans

Abstract: Social relationships may enhance emotional health in older age. The authors examined associations between social relationships and emotional health using data from the Milwaukee African American sample of the second Midlife Development in the United States (MIDUS II) study, 2005-2006 (n = 592). Self-reports indicated good, very good, or excellent emotional health, distinguished from fair or poor. Social relationships were measured by relationship type (family or friend), contact frequency, and levels of emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
5
8
0
Order By: Relevance
“…These findings are consistent with other research on friendships indicating that non-kin peers play important supportive roles for African Americans (Chatters et al, 1994). Consistent with research on self-rated emotional health (Warren-Findlow et al, 2011), this study found that friend support was associated with lower odds of depression even when controlling for family sources of support. Several conclusions can be drawn from this collection of findings.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These findings are consistent with other research on friendships indicating that non-kin peers play important supportive roles for African Americans (Chatters et al, 1994). Consistent with research on self-rated emotional health (Warren-Findlow et al, 2011), this study found that friend support was associated with lower odds of depression even when controlling for family sources of support. Several conclusions can be drawn from this collection of findings.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is somewhat unexpected because structural features of family networks, such as frequency of contact are generally less likely to be associated with health and mental health than subjective measures of social support (Warren-Findlow et al, 2011). In interpreting this finding, it is important to note that contemporary Caribbean Black families are often highly geographically dispersed (i.e., transnational families).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional support, better quality relationships with friends, and greater satisfaction with SS were significantly associated with better mental health (Bloor, Sandler, Martin, Uchino, & Kinney, 2006; Dressler, 1985; Warren-Findlow, Laditka, Laditka, & Thompson, 2011). One study comparing African Americans to Caucasians found the former needed emotional support more than the latter (Bloor et al, 2006).…”
mentioning
confidence: 99%
“…We propose SS acts as a greater buffer for PD among African Americans than Caucasians, so using race as a moderator is more appropriate, because moderators show whether a construct differentially affects groups. Moreover, moderation analyses have the most power when the relation between the predictor and outcome are well established (Frazier et al, 2004), as is the relation between SS and PD (Bloor et al, 2006; Bosworth et al, 2002; Hays et al, 1998; Warren-Findlow et al, 2011). …”
mentioning
confidence: 99%